Emergence of VIM-6 metallo-beta-lactamase-producing Alcaligenes faecalis clinical isolates in a hospital in India - Atul Khajuria; Ashok Kumar Praharaj; Mahadevan Kumar; Naveen Grover (Journal of Infection in Developing Countries)
This item has no abstract. Use the links below to access the full text.